2007
DOI: 10.1007/s10350-006-0728-6
|View full text |Cite
|
Sign up to set email alerts
|

Sonographic Characteristics of Rectal Sensations in Healthy Females

Abstract: The results verified that the internal anal sphincter contributes to the perception of rectal sensations by a relaxation allowing intra-anal bolus to increase the pressure on the anoderm during rectal contraction. A new observation is presented on the time relation between contraction in the distal internal anal sphincter, reversed flow in the anal canal, and the end of rectal sensations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 18 publications
1
4
0
Order By: Relevance
“…These results are in line with those of recent studies using transvaginal ultrasound to visualize the response when rectal content descends into the anal canal8, 11. Both studies support the notion that real‐time functional ultrasound imaging will add important insight into the mechanisms of continence and its disorders, compared with the still‐pictures of the endoanal technique.…”
Section: Discussionsupporting
confidence: 90%
“…These results are in line with those of recent studies using transvaginal ultrasound to visualize the response when rectal content descends into the anal canal8, 11. Both studies support the notion that real‐time functional ultrasound imaging will add important insight into the mechanisms of continence and its disorders, compared with the still‐pictures of the endoanal technique.…”
Section: Discussionsupporting
confidence: 90%
“…Real-time acquisitions of 3D cine loops are then obtained during various maneuvers including rest, squeeze, and Imaging Pelvic Floor Disorders strain. Visualization of organ prolapse and of avulsion of the puborectalis muscle during stress has been reported [31,32].…”
Section: Woodfield Et Almentioning
confidence: 99%
“…The anal mucosa is highly vascularized by the hemorrhoidal vessels and may act as a cushion when pressure in the anal canal is low in the relaxation state18. A Swedish group may have observed some of these dynamics when they showed that the columns of anal mucosa decreased during the rectoanal inhibitory reflex, allowing the content of the ampulla to descend into the anal canal15. The recent study by Roos et al 19 points out that combined tears involving the IAS, EAS and/or anal mucosa are those in which anal incontinence persists.…”
Section: Discussionmentioning
confidence: 99%
“…Transperineal or transvaginal ultrasound has made possible visualization of the anal canal in function. Since the transducer is outside the target organ, the anal mucosa and its role and interaction with the sphincters and puborectal muscle can also be studied4, 15. Application of the vaginal transducer in this study could possibly have interfered with details of the measured outcomes, particularly with the extent of rotation and bending of the anal canal during voluntary squeeze as the transducer straightens the posterior vaginal wall.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation